2001
DOI: 10.1038/sj.cdd.4400827
|View full text |Cite
|
Sign up to set email alerts
|

APRIL, a new member of the tumor necrosis factor family, modulates death ligand-induced apoptosis

Abstract: APRIL (a proliferation-inducing ligand)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 33 publications
2
61
1
2
Order By: Relevance
“…Our results differ from those of Roth et al (2001), who found that APRIL did not promote glioblastoma cell growth in vitro or in vivo. This discrepancy may be due to the material used: we used defined amounts of pure human recombinant soluble trimeric APRIL, whereas Roth et al studied the proliferation rate of glioblastoma cell lines transfected with a construct encoding APRIL.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results differ from those of Roth et al (2001), who found that APRIL did not promote glioblastoma cell growth in vitro or in vivo. This discrepancy may be due to the material used: we used defined amounts of pure human recombinant soluble trimeric APRIL, whereas Roth et al studied the proliferation rate of glioblastoma cell lines transfected with a construct encoding APRIL.…”
Section: Discussioncontrasting
confidence: 57%
“…All eight glioblastoma cell lines used in this study produced APRIL transcripts. In a previous study (Roth et al, 2001), APRIL transcripts were detected in five of the 12 glioblastoma cell lines tested. Our panel of glioblastoma cell lines differed from that used in this previous study, with only the U373MG and T98G cell lines common to both studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PRIL was also shown to provide a proliferative/survival signal to solid tumor cells. Although only modestly detectable in vitro (Hahne et al, 1998;Roth et al, 2001), this activity has been observed significantly in vivo by overexpressing APRIL in tumor cells (Hahne et al, 1998) or by blocking endogenous PRIL (Rennert et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…APRIL is expressed by a subset of immune cells that also produce B-cell activating factor (BAFF): monocytes, macrophages, (Hahne et al, 1998;Nardelli et al, 2001;He et al, 2004;Chu et al, 2007) as well as in some non-immune cells such as epithelial cells and osteoclasts. Moreover, PRIL is abundantly expressed in a variety of tumor cells and tissues, such as lung carcinomas, melanoma (Roth et al, 2001;Stein et al, 2002), lymphoid malignancies (Nardelli et al, 2001;Deshayes et al, 2004;Kern et al, 2004;Moreaux et al, 2004;Chiu et al, 2007;Pelekanou et al, 2008;Yaccoby et al, 2008) and in particular gastrointestinal tumors including rectum, duodenum, colon, stomach and esophagus (Hahne et al, 1998;Kelly et al, 2000).…”
Section: Introductionmentioning
confidence: 99%